Targeting MDR1-P-glycoprotein (MDR1-Pgp) in immunochemotherapy of acute myeloid leukemia (AML) - Maurizio Cianfriglia (Istituto Superiore di Sanità, 2013)
BACKGROUND: Monoclonal antibodies represent the fastest growing sector of pharmaceutical biotechnology and a number of antibody-based biopharmaceuticals have been approved for cancer treatment. However, in many cases the antibodies used for the treatment of tumors offer only a modest survival benefit to cancer patients. AIMS: In the present review-article we intend to analyze: i) the curative regimen gemtuzumab ozogamicin (GO) -mediate characterized by the absence of cytotoxic drugs MDR1-Pgp substrates to overcome the mechanism of action of this multidrug transporter, ii) the safety and efficacy of MDR reversing strategy in AML outcome and, iii) chemical and biological MDR modulators playing a dual relevant medical role as a therapeutic and MDR reversing agents but not yet entered in the clinical setting of AML. Since the similar multidrug transporter protein MDR1-Pgp and its down modulation factors may affect safety and efficacy of already generated antibody drug conjugates (ADCs) a comprehensive overview of the most clinically representative immunoconjugates is reported. DISCUSSION: ADCs represent one of the most promising strategies to enhance the antitumor activity of antibodies. ADCs comprise an antibody (or an antibody fragment) conjugated to a cytotoxic drug via a chemical linker. The therapeutic concept of ADCs is to use an antibody as a vehicle to selectively delivering a cytotoxic drug specifically to a tumor cell, in most cases by means of binding to target cell surface antigen. As a consequence, ADCs have significant potential for enhancing the antitumor activity of "naked" antibodies and reducing the systemic toxicity of the conjugated drugs.